Crowing characteristics of Pelung chickens at different age and body weight - Ruhyat Partasasmita; INDRAWATI Y. ASMARA; DANI GARNIDA (Society for Indonesian Biodiversity, 2020)
Abstract. Asmara IY, Garnida D, Partasasmita R. 2020. Crowing characteristics of Pelung chickens at different age and body weight. Biodiversitas 21: 4339-4344. Crowing characteristics such as duration, frequency, and intensity are important factors to consider in determining a good Pelung. Age and body weight are among other factors being assumed to affect crowing characteristics. The study was conducted to determine the crowing characteristics of different age and body weight. A survey was carried out in Bandung, Cianjur, and Sukabumi Districts, West Java Province, Indonesia in which a total of 98 birds was selected using a purposive technique. The observed parameters were the duration, frequency, and intensity of crowing. The duration was the length of crowing measured by seconds. Frequency is several crowing in a particular time measured by times. Intensity is the magnitude of crowing measured by decibel. The crowing was recorded from 7 AM-2 PM. Data were analyzed using descriptive analysis and Mann-Whitney U Test to compare data differences between research areas. The study found that the crowing duration of Pelung roosters tends to increase in older birds, but the decrease in heavier birds. Crowing frequency increase along with age and body weight. Crowing intensity is similar in different age groups, while the intensity tends to decrease in the heavier group. The results provide evidence that age and body weight of chickens are an important aspect in Pelung contest and age should be considered as a new category in Pelung contest.